Metode Tawazun Efektif dalam Meningkatkan Hafalan Al-Qur'an di Pondok Pesantren Tahfidz - Fadli, Fadli; Pesha, Indry Nirma Yunizul; Hambari, Hambari (VISA: Journal of Vision and Ideas, 2025)
The Tawazun method is an approach or a method that aims to achieve a balance between various aspects of life, both physical, mental, spiritual, and social. In memorizing the Al-Qur'an. The Tawazun method is the optimization of performance functions in the right and left brains with the concept of memorization, namely students memorize new verses using the right brain, then it is then launched by repeating memorization using the left brain. This study aims to examine the Tawazun method in increasing the effectiveness of memorizing the Al-Qur'an. The research method used is a literature study with data collection instruments carried out by referring to proceedings, articles, data and books etc. The results of this study confirm that the method of memorizing the Al-Qur'an using the Tawazun method can be an effective choice. This is evidenced by the findings from the thesis and proceedings as well as Tawazun's book. The results of this study confirm that the method of memorizing the Al-Qur'an using the Tawazun method can be an effective choice. This is evidenced by the findings from the thesis and proceedings as well as Tawazun's book. The results of the study indicate that the approach of memorizing the Al-Qur'an using the Tawazun method can be an effective method in improving the memorization of the Al-Qur'an in Islamic boarding schools.